Effects of Soybean Lecithin on Growth Performance, Intestine Morphology, and Liver Tissue Metabolism in Rock Bream (Oplegnathus fasciatus) Larvae - Tan, Peng; Zhang, Pian; Zhang, Lei; Zhu, Wenliang; Wang, Ligai; Chen, Ruiyi; Zhu, Qihui; Xu, Dongdong (Frontiers in Marine Science, 2022)
Investigations have demonstrated a strong and positive association between dietary intact phospholipid (PL) inclusion and aquatic larval growth, nevertheless, the precise molecular mechanism underlying PL inclusion on growth performance has not been well elucidated. This study aimed to investigate the effects of dietary soybean lecithin (SL) inclusion on growth performance, liver metabolism, resistance to hypoxia stress, and potential molecular mechanisms in rock bream (Oplegnathus fasciatus) larvae. Four types of equal-protein and equal-lipid content microdiets (MDs) were formulated with graded levels of SL to achieve phospholipid levels of (PLs, dry matter) 3.84% (SL0), 6.71% (SL4), 9.38% (SL8), and 12.21% (SL12). Rock bream larvae (25 days post-hatching) were fed the respective MDs for 30 days with three replicates. We found that dietary SL inclusion promoted growth performance, survival rate, and stress resistance to hypoxia stress. The increased dietary SL inclusion improved intestinal structure, as shown by the increased perimeter ratio, muscular thickness, and mucosal fold height of the mid-intestinal tissue. Moreover, a high SL inclusion diet (SL12) increased the activity of the key lipolysis-related enzyme (lipase [LP]) in liver tissue but decreased the activity of amino acid catabolism-related enzymes (aspartate aminotransferase [AST] and alanine aminotransferase [ALT]). RNA sequencing results in liver tissue revealed that the SL12 diet increased the transcriptional level of fatty acid activation-related genes (acsl6 and acsbg2), phospholipid catabolism-related genes (acat2, lpin2, and crls), and amino acid synthesis-related genes (gs, csb, aldh18a1, and oct), but decreased the expression of amino acid catabolism-related gene gprt2. Notably, the SL12 diet significantly increased the expression of ribosome biogenesis-related genes (pes1, nop56, nop58, and rpf2) in liver tissue. The ribosome protein-related pathways were the most enriched pathways mapped in the GO database. Collectively, this study demonstrated the necessity of dietary SL for survival, growth performance, promotion of mid-intestinal morphology, and hypoxia stress during the rock bream larval stage. The SL-induced growth performance promotion was likely attributed to increasing nutrient acquisition by intestinal morphology improvement and to increasing SL catabolism and thereby sparing amino acids for protein synthesis.